Homocitrullination of lysine residues mediated by myeloid-derived suppressor cells in the tumor environment is a target for cancer immunotherapy. Issue 7 (28th July 2021) - Cook, Katherine W; Xue, Wei; Symonds, Peter; Daniels, Ian; Gijon, Mohamed; Boocock, David; Coveney, Clare; Miles, Amanda K; Shah, Sabaria; Atabani, Suha; Choudhury, Ruhul H; Vaghela, Poonam; et al.
Abstract : Background: Homocitrullination is the post-translational modification of lysine that is recognized by T cells. Methods: This study identified homocitrullinated peptides from aldolase, enolase, cytokeratin and binding immunoglobulin protein and used human leukocyte antigen (HLA) transgenic mice to assess immunogenicity by enzyme-linked immunosorbent spot assay. Vaccine efficacy was assessed in tumor therapy studies using HLA-matched B16 melanoma expressing constitutive or interferon γ (IFNγ)-inducible major histocompatibility complex class II (MHC-II) as represented by most human tumors. To determine the mechanism behind the therapy, immune cell infiltrates were analyzed using flow cytometry and therapy studies in the presence of myeloperoxidase (MPO) inhibitor and T-cell depletion performed. We assessed the T-cell repertoire to homocitrullinated peptides in patients with cancer and healthy donors using flow cytometry. Results: Homocitrulline (Hcit) peptide vaccination stimulated strong CD4 T-cell responses and induced significant antitumor therapy in an established tumor model. The antitumor response was dependent on CD4 T cells and the effect was driven mainly via direct tumor recognition, as responses were only observed if the tumors were induced to express MHC-II. In vitro proliferation assays show that healthy donors and patients with cancer have an oligoclonal CD4 T-cell repertoire recognizing homocitrullinated peptides. Inhibition of cyanate generation, which mediates homocitrullination, by MPO inhibition reduced tumor therapy by the vaccine induced T cells (p = 0.0018). Analysis of the tumor microenvironment (TME) suggested that myeloid-derived suppressor cells (MDSCs) were a potential source of MPO. The selected B16 melanoma model showed MDSC infiltration and was appropriate to see if the Hcit vaccine could overcome the immunosuppression associated with MDSCs. The vaccine was very effective (90% survival) as the induced CD4 T cells directly targeted the homocitrullinated tumor and likely reversed the immunosuppressive environment. Conclusion: We propose that MPO, potentially produced by MDSCs, catalyzes the buildup of cyanate in the TME which diffuses into tumor cells causing homocitrullination of cytoplasmic proteins which are degraded and, in the presence of IFNγ, presented by MHC-II for direct CD4 T-cell recognition. Homocitrullinated proteins are a new target for cancer vaccines and may be particularly effective against tumors containing high levels of MPO expressing MDSCs.